Song Lee and the Leech Man - Kline, Suzy.; Remkiewicz, Frank (New York, NY : Scholastic Inc., 1995)
Harry plots revenge against Sidney, the class tattletale, when Miss Mackle's second graders go on a field trip to the pond.
G2
Keywords: Schools -- Fiction; School field trips -- Fiction; Pond animals -- Fiction; Korean-Americans -- Fiction